Peaceful co-existence among the religious minorities of Bangladesh: an analytical study - Muhammad, Saud; Abdul Rahim, Adibah (Research Institute for Islamic Product and Malay Civilization (INSPIRE) Universiti Sultan Zainal Abidin (UniSZA), 2017)
Bangladesh is historically a country of many religious minorities including Hindu, Buddhist, Sheik, Animist, and Atheist. After the liberation war, it contributed immensely to sustain religious, social as well as political harmony among the people of multi religious beliefs. Despite the profound struggles from the government to sustain the harmonious living, some unavoidable incidents have taken place, such as, the assassination of number of atheists by radical Islamic group, attacking on Hindu minorities and destroying their temple, setting fire to Buddhist temples and dozens of homes, and killing of nine Christians in the church. The incidents have raised the question about the fate of religious minorities and peaceful co-existence among all religious sects in Bangladesh. This paper, therefore, attempts at examining the basic problems among all religious groups in Bangladesh that prevent the harmonious living and peaceful co-existence. At the same time, it identifies the forces that play a vital role to spread a religious fanaticism. In addition, the paper evaluates the current situation of Bangladesh in terms of social, political and religious rights of minority groups. In addressing the issue, the paper also provides some recommendations for better religious peaceful co-existence among the people of multi religious beliefs.